230k views
3 votes
Consider the two functions shown below.

Consider the two functions shown below.-example-1

2 Answers

3 votes

Answer: Option B

Then The functions f(x) and g(x) are inverses because
f(g(x))=g(f(x))=x

Explanation:

To answer this question we must make the composition of f (x) and g (x)

We found


f (g(x))

We know that


f(x) = 2x-2\\\\g(x) = (1)/(2)x + 1

By definition if two functions f and g are inverses then it follows that:


f(g(x)) = g(f(x)) = x

So if
f(g(x)) = x f and g are inverse

To find
f(g(x)) enter the function g(x) within the function f(x) as shown below


f(g(x))= 2( (1)/(2)x + 1)-2\\\\f(g(x))= x + 2 -2\\\\f(g(x))= x

Now


g(f(x))= (1)/(2)(2x-2) + 1\\\\g(f(x))= x-1 + 1\\\\g(f(x))= x

Observe that


f(g(x))=g(f(x))=x

Then The functions f(x) and g(x) are inverses because
f(g(x))=g(f(x))=x

User NitZRobotKoder
by
6.1k points
0 votes

ANSWER

B. The functions f(x) and g(x) because f(g(x))=g(f(x))=x

EXPLANATION

The given functions are:


f(x) = 2x - 2

and


g(x) = (1)/(2)x + 1

If f(x) and g(x) are inverses, then

f(g(x))=x


f(g(x))=f( (1)/(2) x + 1)


f(g(x))=2( (1)/(2)x + 1) - 2

Expand the parenthesis to obtain,


f(g(x))=x + 2- 2


f(g(x))=x

Also,


g(f(x)) = g(2x - 2)


g(f(x)) = (1)/(2) (2x - 2) + 1


g(f(x)) = x - 1+ 1


g(f(x)) = x

Hence f(x) and g(x) are inverses

User Nelumbo
by
6.1k points